ISLAM DAN DEMOKRASI: REPRESENTASI DEMOKRASI PASCA PEMILU PADA MEDIA ISLAM - Zakiya Rohma (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Based on the results of the National Survey Board Saiful Mujani Research and Consulting (SMRC) on 20th May-1th June 2019 towards the image of democracy in Indonesia decreased trust from the community after the 22th May riot in front of the KPU office. In June 2019 the community expressed satisfaction with democracy only reaching 66%. Declining public trust lead to democracy in an alarming position especially with the existence of anti-democratic groups who will take advantage of that moment. Besides that, some islamic mass media also represent the image of democracy. Therefore this research to find out how the representation of Islamic media in Indonesia after the 2019 election. The online media analyzed are Nu.or.id and Voa-islam.com using Norman Feirclough’s discourse analysis method. The results showed that the two online media have different representation of democracy in accordance with the interest, political identity and the Islamic group identity.